Sequential healing at implants with different configuration and modified surfaces: an experimental study in the dog - Schweikert, Michael T.; Botticelli, Daniele [UNESP]; Sbricoli, Luca; Antunes, Antonio; Favero, Vittorio; Salata, Luiz A. (Wiley Periodicals, Inc., 2015)
To evaluate the peri-implant soft and hard tissue adaptation at implants with different modified surfaces and configurations. Six Beagle dogs were used. Mandibular premolars and first molars were extracted bilaterally. After 3 months, full-thickness flaps were elevated, and two different types of trans-mucosal implants (ICX-Gold®, Medentis Medical GmbH, Dernau, Germany and SLActive®, Institute Straumann, Bern, Switzerland) and two different surfaces were randomly installed in the distal regions of one side of the mandible. Abutments were applied, and a nonsubmerged healing was allowed. After 1 month, the procedures were performed in the other side of the mandible, and after a further month, the animals were sacrificed, biopsies were collected, and ground sections prepared for histological examination. Similar results in marginal bone and soft tissues dimensions were observed after 1 month of healing at the two implant systems used, and no major changes could be observed after 2 months of healing. After 1 month, the percentage of new bone was 69.0% and 68.8% at ICX-Gold and SLActive surfaces, respectively. After 2 months, the percentage of new bone was 67.8% and 71.9% at ICX-Gold Medentis and SLActive surfaces, respectively. No statistically significant differences in osseointegration were found. The two implant systems used resulted in similar osseointegration after 1 and 2 months of healing.
Keywords: Slactive; Animal study; Bone; Bone healing; Early healing; Histology; Implant dentistry; Implant surface; Nonsubmerged healing; Osseointegration